Effect of calcination temperatures on the electrochemical performances of nickel oxide/reduction graphene oxide (NiO/RGO) composites synthesized by hydrothermal method. (November 2016) - Chen, Gang; Guan, Hongtao; Dong, Chengjun; Xiao, Xuechun; Wang, Yude
Abstract: A series of NiO/RGO composites based on NiO nanoparticles anchored on layered RGO surfaces were proposed by the same hydrothermal method combined with different calcination temperatures (250, 300, 400 and 500 °C). The effects of calcination temperatures on the capacitive behaviors have been discussed by investigating the components, morphologies, surface conditions of the NiO/RGO composites. The specific capacitance values of NiO/RGO composites calcined at 250, 300, 400 and 500 °C are 950, 553, 375 and 205 F/g at the current density of 1 A/g and the corresponding capacitance retention are 91.3%, 83.9%, 71.9% and 67.3% after 1000 cycles at the current density of 10 A/g. The results suggest the calcination temperature plays an important role in the electrochemical performances of NiO/RGO composites and the electrochemical performances were deteriorated with the increasing calcination temperatures. Graphical abstract: NiO/RGO composites synthesized by hydrothermal method combined with the different calcination temperatures exhibit the excellent capacitive behaviors. Highlights: NiO/RGO composites were synthesized under the different calcination temperatures. Calcination temperature impacts capacitive properties as electrode. NiO/RGO composites calcined at low temperature possess the excellent capacitive behaviors. Crystallinity, component and surface defects play major role on capacitive character.